The Effect of Late Publication Financial Statements on Stock Prices with Company Reputation as Moderator in Companies Listed on the IDX Period 2020-2022 - Miwanda Putri, Denik Nadia; Setiawati, Ledy (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
This study aims to analyze the effect of delays in the publication of financial statements on stock prices, by considering corporate reputation as a moderating variable in companies listed on the Indonesia Stock Exchange and have experienced delays in the publication of financial statements in 2020-2022. To test this relationship, this study uses audited annual financial report data of 89 companies that are late and listed on the Indonesia Stock Exchange for the period 2020-2022. This research sample was selected using purposive sampling. Data analysis was carried out using the IBM SPSS 22 analysis tool and using simple linear regression techniques. The results showed that late in publication of financial statements had no significant positive effect on stock prices. This shows that late in the publication of financial statements has no influence on stock prices. This study also found that company reputation is able to moderate the effect of late publication of financial statements on stock prices.